Analysis of Promotion and Product Differentiation of Jukajo on Consumer Purchase Decision - Gandhy, Abel; Hairuddin, Julio Arthur (Bina Nusantara University, 2018)
The purpose of this research was to measure the relationship and the impact of promotion and product differentiation on Jukajo consumer purchase decision. This research was a quantitative research with a questionnaire as the data collection method. The sampling technique in this research is purposive sampling technique. Then, the questionnaire was measured by Likert-scale and multiple linear regression. The result shows that promotion and product differentiation variable have positive impact on purchase decision partially and simultaneously. Bothvariables have 50,5% of impact towards consumer purchase decisions of Jukajo. Moreover, product differentiation becomes the most dominant variable which partially affects consumer purchase decision.